Perspektywy rozwoju gospodarki turystycznej opartej na wiedzy w Polsce - Nawrocka, Elżbieta (The Perspectives of Knowledge Intensive Tourism Economy Development in Poland, 2008)
Contemporary society entered the new epoch i.e. the period of information technology (the construction of information society), diversified structures and segmented culture, while in economy sector there have been observed interdependencies among knowledge, productivity, and economic growth. These processes prove the emergence of knowledge intensive economy. The objective of the hereby article is to analyse these factors which influence the development of knowledge intensive tourism economy in Poland. The article assumes that among conditions influencing the development of knowledge intensive economy one should distinguish mainly the formal-legal, economic, technological and social conditions which occur at the level of the European Union and Poland. The article concludes by presenting recommendations for indispensable changes facilitating broader implementation of knowledge intensive tourist economy concept.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 53-66